The regulation of accounting education in Malaysia: professionalisation of academia and academisation of the profession? - Ismail, Hashanah; Mustapha, Mazlina; Minai, Badriyah (Penerbit Universiti Teknologi Malaysia, 2014)
This paper attempts to conceptualize the relationship between academia and the sole regulating body for accountants in Malaysia, the Malaysian Institute of Accountants, in the supply chain of accounting graduates from local universities to the society of the accounting profession (Chartered Accountants) in Malaysia. There are many routes to becoming an accountant in Malaysia and the Accountants Act 1967 recognizes that only graduates from MIA accredited Accounting degree programs of Malaysian universities can become members of the Malaysian Institute of Accountants without having to acquire any other professional qualifications. This study will trace the quality assurance put in place by the university and the profession to ensure that the graduates do have the requisite skills to join the profession. Over the years other universities started offering accounting programs as well within the framework of the particular university’s philosophy and mission making each university a “brand” name. The proliferation of higher institutions offering accounting programs has prompted the Ministry of Higher Education to initiate the “Way Forward” think tank ( comprising members of the profession and academic representatives) to deliberate on standardization of curriculum contents and delivery process at institutions of higher learning. The results: Halatuju 1 (Way forward 1) 2001-2005, Way forward 2:2007-2013 and forthcoming: Way forward 3. The process of standardization and benchmarking has seen an increasingly prominent role of the profession in setting the scope of academic content, at times bordering on coercion to implement set ways of delivery of content. Has increasing regulation of accounting programmes at universities produced the desired outcome?